Respuesta :

Answer:

[tex]f(x)=x^3-8x^2+13x-6[/tex]

Step-by-step explanation:

We are given information about polynomial as

a root of 1 with multiplicity 2

so, one of factor is (x-1)^2

a root of 6 with multiplicity 1

so, another factor is (x-6)^2

so, we can write polynomial as

[tex]f(x)=(x-1)^2(x-6)[/tex]

now, we can simplify it

[tex]f(x)=(x-1)(x-1)(x-6)[/tex]

[tex]f(x)=(x^2-2x+1)(x-6)[/tex]

So, we get polynomial as

[tex]f(x)=x^3-8x^2+13x-6[/tex]

Answer: f(x) = (x – 1)(x – 1)(x – 6)

Step-by-step explanation: